Investigating the efficiency improvement possibilities of solar systems using systematic literature research - Seres, László; Tamás, Péter (Advanced Logistic Systems - Theory and Practice, 2024)
Today's energy-demanding industrial and residential environment, in view of future challenges, requires more efficient energy production, distribution and network development methods than ever before. In relation to the area, it became necessary to develop new system models and optimization methods, by applying which the planning, installation, logistics, operation and maintenance efficiency of the examined systems can be significantly increased. The important objective of the publication is to analyze and summarize the scientific results found so far on the topic, as well as to identify the scientific gap based on the obtained results.